Training and Assisting in Writing Scientific Papers for Middle School Teachers in Musi Subdistric - Justin Eduardo Simarmata; Lailin Hijriani; Ferdinandus Mone; Hendrika Bete (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The aim of this community service activity is to train and assist junior high school teachers in Musi District to carry out scientific writing activities. The method of implementation in training and mentoring activities for writing scientific papers for Middle School teachers in Musi District consists of several activities which include: preparation, implementation, and evaluation of activities. Community service activities were carried out at Oelneke State Junior High School, Musi District, North Central Timor Regency, East Nusa Tenggara. Participants in community service activities consist of 39 people. Participants consist of the principal and teacher representatives from each school. Training and assisting in writing scientific papers for Middle School teachers in Musi Subdistrict received a positive response from the school and it is expected that it can provide useful knowledge for teachers in compiling scientific papers to be published.